The Long Term Impact of Health on Economic Growth in Pakistan (The Pakistan Development Review, 2008)
Human capital plays pivotal role for sustainable economic Growth. As different growth theories suggest the role of human capital as a significant for growth process. The concept of human capital in economic literature defined broadly by including education, health, training, migration, and other investments that enhance an individual’s productivity. However, the growth economists that have incorporated human capital in the growth studies, paid greater attention on analysing the impact of education on economic growth, while ignoring the role of health human capital. It is only in very recent times that studies have started looking at health and tried to estimate the relationship between health status and economic growth. There exists a two-way relationship between improved health and economic growth. Health and other forms of human and physical capital increases the per capita GDP by increasing productivity of existing resources coupled with resource accumulation and technical change. Furthermore, some part of this increased income is spent on investment in human capital, which results in further per capita growth. According to Fogel (1994), approximately one third of GDP of Britain between 1790 and 1980 is the outcome of improvements in health especially improvement in nutrition, public health, and medical care facilities and these improved health facilities should be considered as labour enhancing technical change.